2015
DOI: 10.1097/cco.0000000000000216
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade epithelial ovarian cancer

Abstract: The results of phase III mitogen-activated protein kinase kinase inhibitor studies in low-grade serous ovarian cancer and further clinical and biological assessment of low-grade endometrioid and mucinous ovarian cancers are urgently required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Due to its unresponsiveness to cytotoxic chemotherapy, treatment of unresectable LGSOC has been a challenge. Alternative treatment modalities including hormonal therapy and anti-angiogenic agent have been studied ( Oswald and Gourley, 2015 ; Gershenson et al, 2009 ; Schmeler et al, 2008 ; Watanabe et al, 2016 ), however, treatment response to hormonal therapy is suboptimal (9%) and bevacizumab studies showed conflicting findings in terms of response-rate even though it did appear that anti-angiogenic treatment prolonged the duration of response ( Oswald and Gourley, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its unresponsiveness to cytotoxic chemotherapy, treatment of unresectable LGSOC has been a challenge. Alternative treatment modalities including hormonal therapy and anti-angiogenic agent have been studied ( Oswald and Gourley, 2015 ; Gershenson et al, 2009 ; Schmeler et al, 2008 ; Watanabe et al, 2016 ), however, treatment response to hormonal therapy is suboptimal (9%) and bevacizumab studies showed conflicting findings in terms of response-rate even though it did appear that anti-angiogenic treatment prolonged the duration of response ( Oswald and Gourley, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade-serous-ovarian-carcinoma(LGSOC) is a rare subtype of epithelial ovarian cancer (EOC) that accounts for 6–10% of serous ovarian cancer and 5–8% of all EOC ( Oswald and Gourley, 2015 ). Multiple studies demonstrated it is histologically, molecularly, and clinically distinct from high-grade-serous-ovarian-cancer (HGSOC) ( Oswald and Gourley, 2015 ; Vang et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless these studies did suggest that clear cell and endometrioid ovarian cancers may be distinguished from serous ovarian cancers based on their gene expression profiles (610). However, many of these early studies included well differentiated tumors (G1) known to be distinct molecular entities (11). To date it is unclear if the evolving signatures which have been used to successfully classify HGSOC into four molecular subtypes could also be used to classify these less common epithelial ovarian cancer histologies.…”
Section: Introductionmentioning
confidence: 99%
“…All low grade tumors were excluded from this study as they are known to represent distinct biologic entities (11). We applied the pre-specified TCGA gene expression signatures and the reduced CLOVAR gene signatures to this cohort of 276 well annotated OCs from Mayo Clinic.…”
Section: Introductionmentioning
confidence: 99%